Generation of single qubit rotation gates using superadiabatic approach - Issoufa, Youssouf Hamidou; Mahmoud Ahmed, Gharib Subhi; Messikh Azeddine, Azeddine (NSP Natural Sciences Publishing Cor., 2015)
We discuss the quantum rotation gates in tripod system. We show that Stimulated Raman Adiabatic Passage (STIRAP) requires high Rabi frequencies to have a perfect rotation gate. Moreover, we improve this process by using superadiabatic approach. This approach requires additional Hamiltonian that can be implemented by driving the tripod with additional fields. Furthermore, we show that it is robust to the decay of the excited state, but not to the dephasing caused by collisions or phase fluctuations of the driving fields.